Measuring Duopoly Power in the British Electricity Spot Market - Wolfram, Catherine D (American Economic Review, 1999)
This article presents an empirical study of market power in the British electricity industry. Estimates of price-cost markups are derived using direct measures of marginal cost and several approaches that do not rely on cost data. Since two suppliers facing inelastic demand dominate the industry, most oligopoly models predict prices substantially above marginal costs. All estimates indicate that prices, while higher than marginal costs, are not nearly as high as most theoretical models predict. Regulatory constraints, the threat of entry, and financial contracts between the suppliers and their customers are considered as possible explanations for the observed price levels. (JEL L13, L94)